Research handbook on empirical studies in intellectual property law - Derclaye, Estelle, 1974- (Research handbooks in intellectual property, 2023)
"This comprehensive Research Handbook explores empirical legal studies of intellectual property law. It covers research from four continents and offers unique conclusions to aid in the creation and understanding of policies and legislation. By combining research from both leading experts and up-and-coming scholars, this expansive Research Handbook examines the four main intellectual property rights: patent, trademark, design and copyright, as well as trade secrets. Chapters provide cutting-edge empirical data and projections on legislation and case law, using quantitative and qualitative methods, including surveys, interviews, descriptive and inferential statistics. The Research Handbook on Empirical Studies in Intellectual Property Law will be highly beneficial for scholars and advanced students of intellectual property, in both legal and economic disciplines, and will inspire new research directions. Practitioners and policymakers will also be interested as the chapters offer statistics on which client advice and policymaking can be based"--